Recognition of Temporal Phenomena from LSST Alert Streams. Issue Volume 14:Issue S339(2018) (November 2017) - Saha, A.
Abstract: LSST will uncover a few million time-domain alerts per night with a latency of a minute. This will provide a huge discovery space, where previously undiscovered rare phenomena may be revealed. The early detection of such previously unknown events from a minimal set of measurements is critical for discovery and follow-up. Analysis methods to recognise such events are being investigated and developed. A discussion of those approaches was presented.